(3eYLe TjhN GHf YSGcQs - (3Ydj Hf GdMSf Hf gHI Gddg GdTGaYj GdOeTbj, CHh GdbGSe, KbI GdOjf, GHf YSGcQ , J (B571 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdMcje GdNGdb GdQRGb s
(3hgPg GdfSNI Yf fSNI GdeUfas
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B273s
(3HQhcdeGf edMb (B- (3GdLRA (B1 - (3U (B567 ; (3agQS GdeNWhWGJ GdeUhQI (B((3eYgO GdeNWhWGJ GdYQHjI(B) - (3LRA JGQjN (B- (3bSe (B1 - (3U (B253 s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
Keywords: (3GdJGQjNs